The Effect of Work Flexibility and Stress on the Performance of Civil Servants during the Covid-19 Pandemic (Study on Employees Aceh Watershed Department) - Ridha Abdillah; Suharnomo Suharnomo (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study aims to examine how much influence the variable flexible work arrangements have on the performance of civil servants at the Aceh Water Service through work stress during the covid-19 pandemic. Data were collected using a survey method through an online questionnaire from a population of 268 employees of the Aceh Water Service with the status of civil servants using a census sampling technique. The data is processed using AMOS 24.0 software to find out the results. The findings show that flexible work arrangements have a positive and significant effect on employee performance, flexible work arrangements have a negative and significant effect on work stress, work stress has a negative and significant effect on employee performance, flexible work arrangements have an indirect effect on employee performance through work stress as a mediation. This research shows that flexible work arrangements are proven to improve employee performance during the pandemic. In addition, work stress will reduce employee performance because flexible work causes multitasking and stress in completing tasks.